Inferring speciation history in the Andes with reduced‐representation sequence data: an example in the bay‐backed antpittas (Aves; Grallariidae; Grallaria hypoleuca s. l.). Issue 24 (15th December 2015) - Winger, Benjamin M.; Hosner, Peter A.; Bravo, Gustavo A.; Cuervo, Andrés M.; Aristizábal, Natalia; Cueto, Luis E.; Bates, John M.
Abstract: In the Andes, humid‐forest organisms frequently exhibit pronounced genetic structure and geographic variation in phenotype, often coincident with physical barriers to dispersal. However, phylogenetic relationships of clades have often been difficult to resolve due to short internodes. Consequently, even in taxa with well‐defined genetic structure, the temporal and geographic sequences of dispersal and vicariance events that led to this differentiation have remained opaque, hindering efforts to test the association between diversification and earth history and to understand the assembly of species‐rich communities on Andean slopes. Here, we use mitochondrial DNA and thousands of short‐read sequences generated with genotyping by sequencing (GBS) to examine the geographic history of speciation in a lineage of passerine birds found in the humid forest of the Andes, the 'bay‐backed' antpitta complex ( Grallaria hypoleuca s. l). Mitochondrial DNA genealogies documented genetic structure among clade but were poorly resolved at nodes relevant for biogeographic inference. By contrast, relationships inferred from GBS loci were highly resolved and suggested a biogeographic history in which the ancestor originated in the northern Andes and dispersed south. Our results are consistent with a scenario of vicariant speciation wherein the range of a widespread ancestor was fragmented as a result of geologic or climatic change, rather than a stepping‐stone series of dispersal events across pre‐existing barriers. However, our study also highlights challenges of distinguishing dispersal‐mediated speciation from static vicariance. Our results further demonstrate the substantial evolutionary timescale over which the diverse biota of the Andes was assembled.